Multi-objective rapid transit network design with modal competition: The case of Concepción, Chile. (February 2017) - Gutiérrez-Jarpa, Gabriel; Laporte, Gilbert; Marianov, Vladimir; Moccia, Luigi
Abstract: We present a mixed integer linear program for the rapid transit network design problem with static modal competition. Previous discrete formulations cannot handle modal competition for realistic size instances because of the complexity of modeling alternatives for each flow in the network. We overcome this difficulty by exploiting a pre-assigned topological configuration. We discuss relevant goals of rapid transit planning, and we propose a multi-objective model conducive to a post-optimization analysis for effectiveness, efficiency, and equity concerns. A case study carried out for a metro proposal in Concepción, Chile, shows the suitability of the proposed method consisting of the mixed integer linear program coupled with the post-optimization analysis. Abstract : Highlights: We model and solve a strategic metro design problem with modal competition. A discrete mathematical program allows a fine modeling of the problem's attributes. A pre-assigned topological configuration allows resolution by integer programming. A multi-objective framework addresses efficiency, effectiveness, and equity concerns. A case study on the city of Concepción illustrates the suitability of the methodology.